2022
DOI: 10.15407/ubj94.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the spectral characteristics, purity and antioxidant activity of C-phycocyanin from the cyanobacteria collected in Kaunas Lagoon (Lithuania)

Abstract: The physicochemical characteristics of phycocyanin extracted from cyanobacteria collected in Kaunas Lagoon were studied (spectrum characteristics, C-PC content in the dry mass and chemical purity). It was determined that the tested concentrations of C-PC in purified water should be in the range of 0.02–0.16% for measuring C-PC content in the dry mass and its spectrum characteristics. The two clear absorption maxima were detected in the spectrum of C-PC at the wavelengths of 277 and 619 nm. The content of C-PC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, it is not clear why the authors showed on the graphs the negative values of antioxidant activity in the DPPH test. As a rule, such values have compounds with prooxidant activity [97]. All the essential oils were cytotoxic for PMNs and PBMCs only at concentrations greater than 0.1 µg/mL in the MTT test.…”
Section: Anti-inflammatory Activitymentioning
confidence: 89%
See 3 more Smart Citations
“…However, it is not clear why the authors showed on the graphs the negative values of antioxidant activity in the DPPH test. As a rule, such values have compounds with prooxidant activity [97]. All the essential oils were cytotoxic for PMNs and PBMCs only at concentrations greater than 0.1 µg/mL in the MTT test.…”
Section: Anti-inflammatory Activitymentioning
confidence: 89%
“…Among the tests used to measure the antioxidant activity of M. piperita is the DPPH test (free radical scavenging activity) [1,12,18,20,63,81,88], β-carotene-linoleic acid assay, NO radical scavenging, reducing power [20], assessment of linoleic acid peroxidation through measurement of thiobarbituric acid reactive substances [1], etc. Antioxidants scavenge radicals through different mechanisms-hydrogen atom transfer or single electron transfer mechanism; or a combination of both mechanisms [16,17,97,98]. The ABTS and ORAC tests are based on the hydrogen atom transfer mechanism.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations